Halogen-free flame-retardant antistatic TPU material and preparation method thereof
By introducing modified graphene, polypyrrole composite materials and epoxidized carbon nanotubes into the TPU resin, a three-dimensional conductive network and a dense carbon layer are constructed, which solves the problem that the flame retardant and mechanical properties of halogen-free flame retardant and antistatic TPU materials cannot be taken into account, and the comprehensive performance improvement of the material is achieved.
Patent Information
- Application Number
- CN202510362919.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing halogen-free flame-retardant anti-static TPU materials have problems that both flame retardant and mechanical properties cannot be taken into account, and the anti-static performance needs to be improved.
By introducing modified graphene, polypyrrole composite materials and epoxidized carbon nanotubes into the TPU resin, a three-dimensional conductive network and a dense carbon layer are constructed to jointly improve flame retardant and mechanical properties, while enhancing anti-static properties.
Halogen-free flame-retardant anti-static TPU materials have been achieved to take into account the flame retardant performance, mechanical properties and anti-static properties, and improve the overall performance of the materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a halogen-free flame-retardant antistatic TPU material and a preparation method thereof. Background Art
[0002] Thermoplastic polyurethane elastomer (TPU) refers to a type of elastomeric block polymer containing repeated carbamate functional groups on the main chain of the macromolecule. Its raw materials are usually oligomer polyols, polyisocyanates, chain extenders / crosslinkers and a small amount of additives. The biggest advantage of TPU material is that its soft and hard segments are composed of different materials, which makes it have both the high elasticity of rubber and the high strength of plastic. TPU is widely used in the furniture industry, construction industry, transportation industry, shoe and leather industry and other fields because of its excellent physical and mechanical properties, wide hardness range, high strength and elastic modulus.
[0003] A Chinese patent (publication number CN114836023B) discloses a flame retardant and antistatic TPU composite material. The invention uses triphenylboroxine as a flame retardant synergist. After adding it to the TPU matrix, it forms a new synergistic flame retardant system with expandable graphene oxide and ammonium polyphosphate, which can overcome the shortcomings of TPU materials being flammable and easy to produce smoke when burning; when a TPU composite material containing 15% of the flame retardant system burns, the polymer can quickly form carbon on the surface without burning; after removing the fire source, it can quickly self-extinguish and has a strong smoke suppression effect; and while significantly improving the flame retardant properties of TPU, it also maintains the original properties of TPU to the greatest extent. However, the halogen-free flame retardant and antistatic TPU materials in the prior art have the problem that the flame retardant properties and mechanical properties cannot be taken into account at the same time, and the antistatic properties need to be improved, which seriously affects their actual use.
[0004] Therefore, how to introduce modified functional components into TPU to prepare halogen-free flame-retardant and antistatic TPU materials to ensure that the materials can take into account both flame retardant properties and mechanical properties while also having good antistatic properties has become a direction that needs to be focused on. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a halogen-free flame retardant and antistatic TPU material and a preparation method thereof, aiming to solve the problem that the flame retardant and mechanical properties of the halogen-free flame retardant and antistatic TPU materials in the prior art cannot be taken into account at the same time, and the antistatic performance needs to be improved.
[0006] The present invention prepares a halogen-free flame-retardant and antistatic TPU material by introducing components such as modified graphene, polypyrrole and carbon nanotubes into TPU resin. By virtue of the synergistic effect of each component, the material can take into account both flame retardant properties and mechanical properties, and also has good antistatic properties.
[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows: In a first aspect of the present invention, a halogen-free flame-retardant antistatic TPU material is provided, comprising the following components in parts by weight: 90-100 parts of TPU resin, 4-8 parts of plasticizer, 2-4 parts of modified graphene, 1-3 parts of polypyrrole, 1-3 parts of carbon nanotubes, 0.4-0.6 parts of 2-hydroxy-4-n-octyloxybenzophenone, 0.2-0.4 parts of antioxidant and 0.2-0.4 parts of polycarbodiimide.
[0008] As a preferred technical solution of the present invention, the weight proportion of the TPU resin can be 90 parts, 92 parts, 94 parts, 96 parts, 98 parts or 100 parts.
[0009] As a preferred technical solution of the present invention, the weight proportion of the plasticizer can be 4 parts, 5 parts, 6 parts, 7 parts or 8 parts.
[0010] As a preferred technical solution of the present invention, the weight proportion of the modified graphene can be 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts.
[0011] As a preferred technical solution of the present invention, the weight proportion of the polypyrrole can be 1 part, 1.5 parts, 2 parts, 2.5 parts or 3 parts.
[0012] As a preferred technical solution of the present invention, the weight proportion of the carbon nanotubes can be 1 part, 1.5 parts, 2 parts, 2.5 parts or 3 parts.
[0013] As a preferred technical solution of the present invention, the weight proportion of the 2-hydroxy-4-n-octyloxybenzophenone can be 0.4 parts, 0.45 parts, 0.5 parts, 0.55 parts or 0.6 parts.
[0014] As a preferred technical solution of the present invention, the weight proportion of the antioxidant can be 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts or 0.4 parts, etc.
[0015] As a preferred technical solution of the present invention, the weight proportion of the polycarbodiimide can be 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts or 0.4 parts.
[0016] As a preferred technical solution of the present invention, the preparation method of the modified graphene includes: adding 1 to 3 parts of zinc nitrate and 4 to 6 parts of 2-methylimidazole, by weight, to 180 to 200 parts of methanol for solvent thermal synthesis to obtain MOFs material; dispersing 10 to 20 parts of commercially available graphene oxide in 400 to 500 parts of deionized water, and then adding 6 to 8 parts of sodium hydroxide and 4 to 6 parts of chloroacetic acid for carboxylation to obtain carboxylated graphene; dispersing 10 to 20 parts of carboxylated graphene in 400 to 500 parts of N, N-dimethylformamide, and then adding 0.2 to 0.4 parts of MOFs material for thermal reaction to obtain modified graphene.
[0017] As a preferred technical solution of the present invention, the conditions of the solvent thermal synthesis treatment include: stirring at 34-38° C. for 18-20 hours, centrifuging, washing with water, and drying.
[0018] As a preferred technical solution of the present invention, the conditions of the carboxylation treatment include: first ultrasonicating at a power of 400-500 W for 2-4 hours, filtering, and then drying at 60-70° C. for 8-10 hours.
[0019] As a preferred technical solution of the present invention, the conditions of the thermal reaction include: stirring at 70-80° C. for 12-14 hours, filtering, washing with water, and drying.
[0020] The carboxylated graphene in the modified graphene can promote cross-linking carbonization during combustion, and its lamellar structure acts as a physical barrier to delay the release of combustible gases. The MOFs material decomposes to generate metal oxides at high temperatures, and the oxygen-containing functional groups of the carboxylated graphene synergistically catalyze the formation of a dense, continuous carbon layer, which effectively isolates heat and oxygen, and the combined effect improves the oxygen index of the TPU material.
[0021] As a preferred technical solution of the present invention, the polypyrrole is a polypyrrole composite material; The preparation method of the polypyrrole composite material comprises: dispersing 2 to 4 parts of MXene powder in 800 to 1000 parts of deionized water by weight, then adding 8 to 12 parts of boric acid and stirring evenly, and then heating to obtain an intermediate product; mixing 100 to 120 parts of deionized water and 100 to 120 parts of isopropanol evenly, then adding 2 to 4 parts of the intermediate product and 30 to 36 parts of pyrrole for magnetic stirring and ultrasonication to obtain liquid A; adding 50 to 60 parts of ammonium persulfate to 200 to 240 parts of liquid A for stirring reaction to obtain the polypyrrole composite material.
[0022] As a preferred technical solution of the present invention, the conditions of the heat treatment include: heating at 170-180° C. for 12-16 hours, centrifuging, washing with water, and vacuum drying.
[0023] As a preferred technical solution of the present invention, the stirring reaction conditions include: controlling the temperature to 0-4°C, stirring at a speed of 80-100 r / min for 20-24 hours, washing with water, freeze-drying, and crushing.
[0024] Polypyrrole in polypyrrole composite materials is a conductive polymer that can construct a conductive path in the TPU matrix, while MXene material has excellent conductivity and can cooperate with polypyrrole to construct a three-dimensional conductive network and quickly release static charges. At the same time, boron doping can adjust the electronic structure of MXene and polypyrrole, enhance the conductive properties, and reduce the surface resistivity of the material, thereby improving the antistatic properties.
[0025] As a preferred technical solution of the present invention, the carbon nanotubes are epoxidized carbon nanotubes; The preparation method of the epoxidized carbon nanotubes comprises: by weight, acidifying 4 to 6 parts of commercially available carbon nanotubes, dispersing the carbon nanotubes in 280 to 300 parts of N,N-dimethylformamide, adding 10 to 20 parts of epoxy resin and stirring the mixture evenly, and then adding 0.4 to 0.6 parts of triphenylphosphine for epoxidation to obtain the epoxidized carbon nanotubes.
[0026] As a preferred technical solution of the present invention, the carbon nanotubes have a tube length of 10 to 20 μm.
[0027] As a preferred technical solution of the present invention, the epoxidation treatment conditions include: first ultrasonication for 30-40 minutes, then heating to 80-90°C and stirring for 20-24 hours, cooling, washing with dichloromethane, and drying.
[0028] As a preferred technical solution of the present invention, the acidification treatment conditions include: adding 4 to 6 parts of commercially available carbon nanotubes to a mixture of 150 to 180 parts of nitric acid and 50 to 60 parts of sulfuric acid, ultrasonically dispersing for 6 to 8 hours, centrifuging, washing with water, and vacuum drying.
[0029] The epoxy groups on the surface of epoxidized carbon nanotubes can react with amino groups, hydroxyl groups, etc. in the molecular chain of TPU groups, and enhance the bonding force between epoxidized carbon nanotubes and TPU matrix through strong interfacial interactions, thereby improving the overall mechanical properties of the composite material and effectively increasing the tensile strength.
[0030] As a preferred technical solution of the present invention, the plasticizer is selected from any one of dioctyl terephthalate, triphenyl phosphate and tricresyl phosphate.
[0031] As a preferred technical solution of the present invention, the antioxidant is antioxidant 1010 or antioxidant 1076.
[0032] The second aspect of the present invention provides a method for preparing the halogen-free flame-retardant antistatic TPU material as described in the first aspect, comprising the following steps: In parts by weight, 90-100 parts of TPU resin, 2-4 parts of modified graphene, 1-3 parts of polypyrrole and 1-3 parts of carbon nanotubes are placed in a mixer and fully mixed, and then 4-8 parts of plasticizer, 0.4-0.6 parts of 2-hydroxy-4-n-octyloxybenzophenone, 0.2-0.4 parts of antioxidant and 0.2-0.4 parts of polycarbodiimide are added, and extrusion granulation is carried out through a twin-screw extruder, and vacuum drying is carried out to obtain a halogen-free flame retardant and antistatic TPU material.
[0033] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adds a variety of modified components to the TPU matrix, wherein the carboxyl groups introduced into the modified graphene by carboxylation treatment can not only combine with the nitrogen atoms on the polypyrrole through coordination, but also react with the epoxy groups modified on the surface of the epoxidized carbon nanotubes. At the same time, the aromatic ring structure in the graphene can undergo π-π conjugation with the heterocyclic rings of the polypyrrole and the graphitized structure of the carbon nanotubes, thereby constructing a three-dimensional conductive network in the matrix, effectively reducing the volume resistance of the material and improving the antistatic performance. The network structure can also limit the movement of the molecular chain and improve the tensile strength.
[0034] (2) In the TPU material of the present invention, under high temperature conditions, the two-dimensional layer structure of graphene migrates to the surface of the material during combustion to form a continuous carbon layer, while the high thermal conductivity and high aspect ratio of epoxidized carbon nanotubes enable them to quickly conduct heat and avoid heat accumulation. The metal ions in the MOFs material have good catalytic properties, which help to generate a denser and more stable carbon layer. The boron element in the polypyrrole composite material can form a dense glass-like protective layer on the polymer surface under high temperature conditions. The MXene material can undergo a decomposition reaction to absorb a large amount of heat, thereby reducing the surface temperature of the material. Through the synergistic effect of multiple components, the flame retardant properties are improved.
[0035] (3) The carboxylated graphene in the modified graphene of the present invention can promote cross-linking carbonization during combustion, and its lamellar structure acts as a physical barrier to delay the release of combustible gases. The MOFs material decomposes to generate metal oxides at high temperatures, and the oxygen-containing functional groups of the carboxylated graphene synergistically catalyze the formation of a dense, continuous carbon layer, which effectively isolates heat and oxygen. The combined effect improves the oxygen index of the TPU material.
[0036] (4) The polypyrrole in the polypyrrole composite material of the present invention is a conductive polymer that can construct a conductive path in the TPU matrix, while the MXene material has excellent conductivity and can cooperate with polypyrrole to construct a three-dimensional conductive network and quickly release static charges. At the same time, boron doping can adjust the electronic structure of MXene and polypyrrole, enhance the conductive properties, and reduce the surface resistivity of the material, thereby improving the antistatic performance.
[0037] (5) The epoxy groups on the surface of the epoxidized carbon nanotubes of the present invention can react with the amino groups, hydroxyl groups, etc. in the molecular chain of the TPU group, thereby enhancing the bonding force between the epoxidized carbon nanotubes and the TPU matrix through strong interfacial interactions, thereby improving the overall mechanical properties of the composite material and effectively increasing the tensile strength. DETAILED DESCRIPTION
[0038] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0039] The sources of some components in the embodiments and comparative examples are as follows: TPU resin, model T5160, purchased from Shandong Yinuowei Polyurethane Co., Ltd.; Dioctyl terephthalate, CAS No. 6422-86-2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Triphenyl phosphate, CAS No. 115-86-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Tricresyl phosphate, CAS No. 1330-78-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Commercially available graphene oxide, product number G476622, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Commercially available polypyrrole, product number P476334, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Commercially available carbon nanotubes I, model TF320, tube length 12 μm, purchased from Shandong Tanfeng New Materials Technology Co., Ltd.; Commercially available carbon nanotube II, model TF1000, tube length 120 μm, purchased from Shandong Tanfeng New Materials Technology Co., Ltd.; 2-Hydroxy-4-n-octyloxybenzophenone, CAS No. 1843-05-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Antioxidant 1010, product number P136696, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Antioxidant 1076, product number I106561, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Polycarbodiimide, CAS No. 151-51-9, was purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.; Zinc nitrate, CAS No. 10196-18-6, from Sinopharm Chemical Reagent Co., Ltd.; 2-Methylimidazole, CAS No. 693-98-1, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Methanol, CAS No. 67-56-1, from Sinopharm Chemical Reagent Co., Ltd.; Sodium hydroxide, CAS No. 1310-73-2, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Chloroacetic acid, CAS No. 79-11-8, from Sinopharm Chemical Reagent Co., Ltd.; N,N-dimethylformamide, CAS No. 68-12-2, from Sinopharm Chemical Reagent Co., Ltd.; MXene powder, product number 103285, was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Isopropyl alcohol, CAS No. 67-63-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Pyrrole, CAS No. 109-97-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Ammonium persulfate, CAS No. 7727-54-0, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Epoxy resin, brand 6101 (E44), purchased from Jiangyin Wanqian Chemicals Co., Ltd.; Triphenylphosphine, CAS No. 603-35-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0040] Example 1 This embodiment provides a halogen-free flame-retardant antistatic TPU material, which includes the following components in parts by weight: 100 parts of TPU resin, 8 parts of plasticizer dioctyl terephthalate, 4 parts of modified graphene, 3 parts of polypyrrole composite material, 3 parts of epoxidized carbon nanotubes, 0.6 parts of 2-hydroxy-4-n-octyloxybenzophenone, 0.4 parts of antioxidant 1010 and 0.4 parts of polycarbodiimide.
[0041] Preparation of the modified graphene: by weight, 3 parts of zinc nitrate and 6 parts of 2-methylimidazole are added to 200 parts of methanol for solvent thermal synthesis treatment, stirred at 38°C for 18 hours, centrifuged, washed with water, and dried to obtain MOFs material; 20 parts of commercially available graphene oxide are dispersed in 500 parts of deionized water, and then 8 parts of sodium hydroxide and 6 parts of chloroacetic acid are added for carboxylation treatment, first ultrasonicated at a power of 500 W for 2 hours, filtered, and then dried at 70°C for 8 hours to obtain carboxylated graphene; 20 parts of carboxylated graphene are dispersed in 500 parts of N,N-dimethylformamide, and then 0.4 parts of MOFs material are added for thermal reaction, stirred at 80°C for 12 hours, filtered, washed with water, and dried to obtain modified graphene.
[0042] Preparation of the polypyrrole composite material: by weight, 4 parts of MXene powder are dispersed in 1000 parts of deionized water, and then 12 parts of boric acid are added and stirred evenly, and then heat-treated, heated at 180° C. for 12 hours, centrifuged, washed with water, and vacuum-dried to obtain an intermediate product; 120 parts of deionized water and 120 parts of isopropanol are mixed evenly, and then 4 parts of the intermediate product and 36 parts of pyrrole are added for magnetic stirring and ultrasonication to obtain liquid A; 60 parts of ammonium persulfate are added to 240 parts of liquid A for stirring reaction, the temperature is controlled at 4° C., stirred at a speed of 100 r / min for 20 hours, washed with water, freeze-dried, and crushed to obtain a polypyrrole composite material.
[0043] Preparation of the epoxidized carbon nanotubes: 6 parts by weight of commercially available carbon nanotubes I (model TF320, tube length of 12 μm) are added to a mixture of 180 parts of nitric acid and 60 parts of sulfuric acid, ultrasonically dispersed for 8 hours, centrifuged, washed with water, vacuum dried, and then dispersed in 300 parts of N,N-dimethylformamide, 20 parts of epoxy resin are added and stirred evenly, and then 0.6 parts of triphenylphosphine are added for epoxidation treatment, first ultrasonically treated for 40 minutes, then heated to 90°C and stirred for 20 hours, cooled, washed with dichloromethane, and dried to obtain epoxidized carbon nanotubes.
[0044] Example 2 This embodiment provides a halogen-free flame-retardant antistatic TPU material, which includes the following components in parts by weight: 90 parts of TPU resin, 4 parts of plasticizer triphenyl phosphate, 2 parts of modified graphene, 1 part of polypyrrole composite material, 1 part of epoxidized carbon nanotube, 0.4 parts of 2-hydroxy-4-n-octyloxybenzophenone, 0.2 parts of antioxidant 1076 and 0.2 parts of polycarbodiimide.
[0045] The preparation method of the modified graphene includes: adding 1 part of zinc nitrate and 4 parts of 2-methylimidazole to 180 parts of methanol by weight for solvent thermal synthesis treatment, stirring at 34°C for 20 hours, centrifuging, washing with water, and drying to obtain MOFs material; dispersing 10 parts of commercially available graphene oxide in 400 parts of deionized water, then adding 6 parts of sodium hydroxide and 4 parts of chloroacetic acid for carboxylation treatment, first ultrasonicating at a power of 400 W for 4 hours, filtering, and then drying at 60°C for 10 hours to obtain carboxylated graphene; dispersing 10 parts of carboxylated graphene in 400 parts of N,N-dimethylformamide, then adding 0.2 parts of MOFs material for thermal reaction, stirring at 70°C for 14 hours, filtering, washing with water, and drying to obtain modified graphene.
[0046] Preparation of the polypyrrole composite material: by weight, 2 parts of MXene powder are dispersed in 800 parts of deionized water, then 8 parts of boric acid are added and stirred evenly, and then heat treatment is performed, heated at 170°C for 16 hours, centrifuged, washed with water, and vacuum dried to obtain an intermediate product; 100 parts of deionized water and 100 parts of isopropanol are mixed evenly, then 2 parts of the intermediate product and 30 parts of pyrrole are added for magnetic stirring and ultrasonication to obtain liquid A; 50 parts of ammonium persulfate are added to 200 parts of liquid A for stirring reaction, the temperature is controlled to 0°C, stirred at a speed of 80r / min for 24 hours, washed with water, freeze-dried, and crushed to obtain a polypyrrole composite material.
[0047] Preparation of the epoxidized carbon nanotubes: 4 parts by weight of commercially available carbon nanotubes I (model TF320, tube length of 12 μm) are added to a mixture of 150 parts of nitric acid and 50 parts of sulfuric acid, ultrasonically dispersed for 6 hours, centrifuged, washed with water, vacuum dried, and then dispersed in 280 parts of N,N-dimethylformamide, 10 parts of epoxy resin are added and stirred evenly, and then 0.4 parts of triphenylphosphine are added for epoxidation treatment, first ultrasonically treated for 30 minutes, then heated to 80°C and stirred for 24 hours, cooled, washed with dichloromethane, and dried to obtain epoxidized carbon nanotubes.
[0048] Example 3 This embodiment provides a halogen-free flame-retardant antistatic TPU material, which includes the following components in parts by weight: 95 parts of TPU resin, 6 parts of plasticizer tricresyl phosphate, 3 parts of modified graphene, 2 parts of polypyrrole composite material, 2 parts of epoxidized carbon nanotubes, 0.5 parts of 2-hydroxy-4-n-octyloxybenzophenone, 0.3 parts of antioxidant 1010 and 0.3 parts of polycarbodiimide.
[0049] The preparation method of the modified graphene includes: adding 2 parts of zinc nitrate and 5 parts of 2-methylimidazole to 190 parts of methanol by weight for solvent thermal synthesis treatment, stirring at 36°C for 19 hours, centrifuging, washing with water, and drying to obtain MOFs material; dispersing 15 parts of commercially available graphene oxide in 450 parts of deionized water, then adding 7 parts of sodium hydroxide and 5 parts of chloroacetic acid for carboxylation treatment, first ultrasonicating at a power of 450W for 3 hours, filtering, and then drying at 65°C for 9 hours to obtain carboxylated graphene; dispersing 15 parts of carboxylated graphene in 450 parts of N,N-dimethylformamide, then adding 0.3 parts of MOFs material for thermal reaction, stirring at 75°C for 13 hours, filtering, washing with water, and drying to obtain modified graphene.
[0050] Preparation of the polypyrrole composite material: by weight, 3 parts of MXene powder are dispersed in 900 parts of deionized water, and then 10 parts of boric acid are added and stirred evenly, and then heat-treated, heated at 175° C. for 14 hours, centrifuged, washed with water, and vacuum-dried to obtain an intermediate product; 110 parts of deionized water and 110 parts of isopropanol are mixed evenly, and then 3 parts of the intermediate product and 33 parts of pyrrole are added for magnetic stirring and ultrasonication to obtain liquid A; 55 parts of ammonium persulfate are added to 220 parts of liquid A for stirring reaction, the temperature is controlled at 2° C., stirred at a speed of 90 r / min for 22 hours, washed with water, freeze-dried, and crushed to obtain a polypyrrole composite material.
[0051] Preparation of the epoxidized carbon nanotubes: 5 parts by weight of commercially available carbon nanotubes I (model TF320, tube length of 12 μm) are added to a mixture of 165 parts of nitric acid and 55 parts of sulfuric acid, ultrasonically dispersed for 7 hours, centrifuged, washed with water, vacuum dried, and then dispersed in 90 parts of N,N-dimethylformamide, 15 parts of epoxy resin are added and stirred evenly, and then 0.5 parts of triphenylphosphine are added for epoxidation treatment, first ultrasonicated for 35 minutes, then heated to 85°C and stirred for 22 hours, cooled, washed with dichloromethane, and dried to obtain epoxidized carbon nanotubes.
[0052] Example 4 This embodiment provides a TPU material, which is different from Embodiment 1 in that commercially available polypyrrole (article number P476334) is used instead of the polypyrrole composite material.
[0053] Example 5 This embodiment provides a TPU material, which differs from Embodiment 1 in that commercially available carbon nanotubes I (model TF320, tube length of 12 μm) are used instead of epoxidized carbon nanotubes.
[0054] Example 6 This embodiment provides a TPU material, which differs from Embodiment 1 in that commercially available carbon nanotubes II (model TF1000, tube length 120 μm) are used instead of commercially available carbon nanotubes I (model TF320, tube length 12 μm) to prepare epoxidized carbon nanotubes.
[0055] Comparative Example 1 This comparative example provides a TPU material, which differs from Example 1 in that 4 parts of modified graphene are not added.
[0056] Comparative Example 2 This comparative example provides a TPU material, which is different from Example 1 in that 3 parts of the polypyrrole composite material are not added.
[0057] Comparative Example 3 This comparative example provides a TPU material, which differs from Example 1 in that 3 parts of epoxidized carbon nanotubes are not added.
[0058] The performance of the TPU materials provided in the above embodiments and comparative examples was tested, and the specific testing method is as follows: (1) Flame retardant performance test: refer to the requirements of GB / T 2406.2-2009 Plastics Oxygen Index Method for Determination of Combustion Behavior Part 2: Room Temperature Test for testing.
[0059] (2) Antistatic performance test: Test according to the requirements of GB / T 31838.3-2019 Dielectric and resistive properties of solid insulating materials Part 3: Resistance characteristics (DC method) Surface resistance and surface resistivity.
[0060] (3) Tensile strength test: Test according to the requirements of GB / T 1040.1-2018 Determination of tensile properties of plastics Part 1: General.
[0061] The above performance test data is shown in Table 1.
[0062]
[0063] From the above content, it can be seen that the present invention introduces modified graphene, polypyrrole composite materials and epoxidized carbon nanotubes and other components into TPU resin to prepare halogen-free flame retardant and antistatic TPU materials (Examples 1 to 3), which have better comprehensive performance, an oxygen index of 33.1 to 33.8%, a surface resistance of 4.5×106 to 5.3×106Ω, and a tensile strength of 66.7 to 67.1MPa.
[0064] Compared with Example 1, commercially available polypyrrole (article number P476334) was used to replace the polypyrrole composite material, and the oxygen index was reduced, the surface resistance was increased, and the tensile strength was reduced (Example 4); compared with Example 1, commercially available carbon nanotubes I (model TF320, tube length of 12 μm) were used to replace the epoxidized carbon nanotubes, and the oxygen index was reduced, the surface resistance was increased, and the tensile strength was reduced (Example 5); compared with Example 1, commercially available carbon nanotubes II (model TF1000, tube length of 120 μm) were used to replace the commercially available carbon nanotubes I (model TF320, tube length of 12 μm) for epoxidation. Preparation of carbon nanotubes. Since the tube length of commercially available carbon nanotubes II is too large and the modification effect is not good, the oxygen index is reduced, the surface resistance is increased, and the tensile strength is reduced (Example 6); compared with Example 1, 4 parts of modified graphene are not added, the oxygen index is reduced, the surface resistance is increased, and the tensile strength is reduced (Comparative Example 1); compared with Example 1, 3 parts of polypyrrole composite materials are not added, the oxygen index is reduced, the surface resistance is increased, and the tensile strength is reduced (Comparative Example 2); compared with Example 1, 3 parts of epoxidized carbon nanotubes are not added, the oxygen index is reduced, the surface resistance is increased, and the tensile strength is reduced (Comparative Example 3).
[0065] In summary, the present invention prepares a halogen-free flame-retardant and antistatic TPU material by introducing components such as modified graphene, polypyrrole composite materials and epoxidized carbon nanotubes into TPU resin. By virtue of the synergistic effect of each component, the material can take into account both flame retardant properties and mechanical properties, and also has good antistatic properties.
Claims
1. A halogen-free flame-retardant antistatic TPU material, characterized in that: In parts by weight, it includes the following components: 90-100 parts of TPU resin, 4-8 parts of plasticizer, 2-4 parts of modified graphene, 1-3 parts of polypyrrole, 1-3 parts of carbon nanotubes, 0.4-0.6 parts of 2-hydroxy-4-n-octyloxybenzophenone, 0.2-0.4 parts of antioxidant and 0.2-0.4 parts of polycarbodiimide; The preparation method of the modified graphene comprises: adding 1 to 3 parts of zinc nitrate and 4 to 6 parts of 2-methylimidazole to 180 to 200 parts of methanol for solvent thermal synthesis to obtain MOFs material; dispersing 10 to 20 parts of commercially available graphene oxide in 400 to 500 parts of deionized water, and then adding 6 to 8 parts of sodium hydroxide and 4 to 6 parts of chloroacetic acid for carboxylation to obtain carboxylated graphene; dispersing 10 to 20 parts of carboxylated graphene in 400 to 500 parts of N,N-dimethylformamide, and then adding 0.2 to 0.4 parts of MOFs material for thermal reaction to obtain modified graphene.
2. The halogen-free flame-retardant antistatic TPU material according to claim 1, characterized in that: The solvent thermal synthesis treatment conditions include: stirring at 34-38° C. for 18-20 hours, centrifuging, washing with water, and drying.
3. The halogen-free flame-retardant antistatic TPU material according to claim 1, characterized in that: The conditions of the carboxylation treatment include: firstly ultrasonicating at a power of 400-500 W for 2-4 hours, filtering, and then drying at 60-70° C. for 8-10 hours.
4. The halogen-free flame-retardant antistatic TPU material according to claim 1, characterized in that: The polypyrrole is a polypyrrole composite material; The preparation method of the polypyrrole composite material comprises: dispersing 2 to 4 parts of MXene powder in 800 to 1000 parts of deionized water, adding 8 to 12 parts of boric acid, stirring evenly, and then heating to obtain an intermediate product; 100-120 parts of deionized water and 100-120 parts of isopropanol are uniformly mixed, and then 2-4 parts of the intermediate product and 30-36 parts of pyrrole are added for magnetic stirring and ultrasonication to obtain liquid A; 50-60 parts of ammonium persulfate are added to 200-240 parts of liquid A for stirring reaction to obtain a polypyrrole composite material.
5. The halogen-free flame-retardant antistatic TPU material according to claim 4, characterized in that: The conditions of the heat treatment include: heating at 170-180° C. for 12-16 hours, centrifuging, washing with water, and vacuum drying.
6. The halogen-free flame-retardant antistatic TPU material according to claim 4, characterized in that: The stirring reaction conditions include: controlling the temperature to 0-4° C., stirring at a speed of 80-100 r / min for 20-24 h, washing with water, freeze-drying, and crushing.
7. The halogen-free flame-retardant antistatic TPU material according to claim 1, characterized in that: The carbon nanotubes are epoxidized carbon nanotubes; The preparation method of the epoxidized carbon nanotubes comprises: acidifying 4 to 6 parts of commercially available carbon nanotubes by weight, dispersing them in 280 to 300 parts of N,N-dimethylformamide, adding 10 to 20 parts of epoxy resin and stirring them evenly, and then adding 0.4 to 0.6 parts of triphenylphosphine for epoxidation to obtain epoxidized carbon nanotubes; The carbon nanotubes have a tube length of 10-20 μm.
8. The halogen-free flame-retardant antistatic TPU material according to claim 7, characterized in that: The epoxidation treatment conditions include: first ultrasonication for 30-40 minutes, then heating to 80-90° C. and stirring for 20-24 hours, cooling, washing with dichloromethane, and drying.
9. The halogen-free flame-retardant antistatic TPU material according to claim 1, characterized in that: The plasticizer is selected from any one of dioctyl terephthalate, triphenyl phosphate and tricresyl phosphate.
10. A method for preparing the halogen-free flame-retardant antistatic TPU material according to any one of claims 1 to 9, characterized in that: The following steps are involved: In parts by weight, 90-100 parts of TPU resin, 2-4 parts of modified graphene, 1-3 parts of polypyrrole and 1-3 parts of carbon nanotubes are placed in a mixer and fully mixed, and then 4-8 parts of plasticizer, 0.4-0.6 parts of 2-hydroxy-4-n-octyloxybenzophenone, 0.2-0.4 parts of antioxidant and 0.2-0.4 parts of polycarbodiimide are added, and extrusion granulation is carried out through a twin-screw extruder, and vacuum drying is carried out to obtain a halogen-free flame retardant and antistatic TPU material.
Citation Information
Patent Citations
A flame-retardant and antistatic TPU composite material
CN114836023B
High-intensity wollastonite fiber plastic and preparation method thereof
CN108530751A
Antibacterial antistatic TPU film material and preparation method thereof
CN109096740A
Flame-retardant smoke-suppressing thermoplastic polyurethane antistatic composite material and preparation method thereof
CN109988411A
Synergistic flame retardant as well as preparation method and application thereof
CN113861433A
Cited By
High-transparency and high-flame-retardancy antistatic TPU (thermoplastic polyurethane) film and preparation method thereof
CN121108725A
A halogen-free antistatic composition for pressure sensitive adhesive
CN122628686A